2021
DOI: 10.1177/1524838020985550
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of Women Survivors of Childhood Sexual Abuse in Relation to Nonsupportive Significant Adults: A Scoping Review

Abstract: Childhood sexual abuse (CSA) is a complex trauma with devastating long-term, negative effects on survivors. This study extended the understanding of experiences of women survivors of CSA in relation to nonsupportive significant adults documented in literature, as to date, there exists no summary in literature on this particular topic. As such, a scoping review was conducted on publications between 1980 and January 2020. A total of 26 733 were selected for analysis in accordance with the search terms. After dup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 71 publications
(187 reference statements)
0
2
0
Order By: Relevance
“…Since 2017, the international Metoo movement has contributed to freeing women's voices about sexual violence [1][2][3]. However, domestic or sexual violence is still difficult to verbalize for survivors and associated with a lack of social and emotional support [4][5][6][7]. A controlled trial in the US showed that following sexual assault, survivors were more reduced to silence and stigmatized than after physical violence [8].…”
Section: Introductionmentioning
confidence: 99%
“…Since 2017, the international Metoo movement has contributed to freeing women's voices about sexual violence [1][2][3]. However, domestic or sexual violence is still difficult to verbalize for survivors and associated with a lack of social and emotional support [4][5][6][7]. A controlled trial in the US showed that following sexual assault, survivors were more reduced to silence and stigmatized than after physical violence [8].…”
Section: Introductionmentioning
confidence: 99%
“…Since 2017, the international Metoo movement has contributed to freeing women's voices about sexual violence [1][2][3]. However, domestic or sexual violence remain di cult to verbalize for survivors and are associated with a lack of social and emotional support [4][5][6][7]. A controlled trial in the US showed that following sexual assault, survivors were more reduced to silence and stigmatized than after physical violence [8].…”
Section: Introductionmentioning
confidence: 99%